Seed polymorphism and effect of GA, on seed germination and seedling growth in Eclipta alba - SUSHAMA KEDIA; PAWAN K. KASERA; SHER MOHAMMED (Seed Research, 2026)
A study on the seed morphology and influence of gibberellic acid (GA) on the germination (%) and seedling growth of Eclipta alba was conducted. Results revealed that seeds were polymorphic in nature. Three types of seeds, viz. black, dark brown and light brown were observed, which differed in their size, weight, viability and germination behaviour. Among these, black seeds showed maximum size, weight, viability, germination (%) and seedling growth. 5 mg 1-1 concentration of GA, was most suitable for obtaining highest germination (%), shoot and root lengths, germination value (GV) and vigour index (VI) in fresh and 6 month old seeds.